2022
DOI: 10.1101/2022.07.15.500224
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gibberellins promote polar auxin transport to regulate stem cell fate decisions in cambium

Abstract: Vascular cambium contains bifacial stem cells, which produce secondary xylem to one side and secondary phloem to the other. However, how these fate decisions are regulated is unknown. Here, we show that the positioning of an auxin signalling maximum within the cambium determines the fate of stem cell daughters. The position is modulated by gibberellin-regulated, PIN1-dependent polar auxin transport. Gibberellin treatment broadens auxin maximum from the xylem side of the cambium towards the phloem. As a result,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 72 publications
1
9
0
Order By: Relevance
“…Moreover, the 35S:PtoGAI plants showed inhibited proliferation and differentiation of the vascular cambium, as well as inhibition of the transition from primary vascular tissue to SVT (Figure 4E, F). Previous studies also found that cambium-specific promoter-driven degradationresistant versions of RGL1 (pWOX4a:ΔRGL1) or RGA (pANT: ΔRGA17) inhibited cambium division and xylem differentiation (Hu et al, 2022;Mäkilä et al, 2023). Therefore, overexpression of DELLAs or inhibition of DELLA degradation suppresses the proliferation of cambium and differentiation into xylem.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…Moreover, the 35S:PtoGAI plants showed inhibited proliferation and differentiation of the vascular cambium, as well as inhibition of the transition from primary vascular tissue to SVT (Figure 4E, F). Previous studies also found that cambium-specific promoter-driven degradationresistant versions of RGL1 (pWOX4a:ΔRGL1) or RGA (pANT: ΔRGA17) inhibited cambium division and xylem differentiation (Hu et al, 2022;Mäkilä et al, 2023). Therefore, overexpression of DELLAs or inhibition of DELLA degradation suppresses the proliferation of cambium and differentiation into xylem.…”
Section: Discussionmentioning
confidence: 92%
“…The PIN auxin efflux carriers act primarily in controlling how auxin accumulates in various tissues during plant development (Adamowski and Friml, 2015). It has been reported that GA regulates PIN transcription in the root apical meristem and vascular cambium (Björklund et al, 2007; Willige et al, 2011; Löfke et al, 2013; Mäkilä et al, 2023). In the vascular tissues of unpeeled Populus , PIN1 is predominantly localized in the cambial regions (Figure S8), which is consistent with the results observed in Arabidopsis (Gälweiler et al, 1998).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations